PERTANGGUNGJAWABAN PEMEGANG LISENSI-WAJIB MENURUT UNDANG-UNDANG NOMOR 14 TAHUN 2001 TENTANG PATEN - Indi Fandaya; Runtung Sitepu; Keizerina Devi Azwar; Utari Maharany Barus (Universitas Sumatera Utara, 2017)
ABSTRACT Patent term first appeared in Europe in the Dark Ages as technologies used. Patent term itself comes from the Greek word meaning 'open'. In the UK the term known letters Patent, namely the decree issued by the kingdom which gives exclusive rights to certain individuals and businesses. From the definition of the word itself Patents, Patents concept to open knowledge for the betterment of society and instead, inventors obtain exclusive rights for a certain period. Problems in this thesis is Do the terms of compulsory patent licensing according to the principles contained in the Intellectual Property Rights? How is the government's role in determining the amount of royalties for a compulsory license? The results showed a condition of the terms of the license shall not fully in accordance with the principles of intellectual property rights, this is due to the loss of the principle of justice on the owner or holder of patents when patent that has been discovered or produced by the owner or holder of patents taken over by government simply because of the pressing needs and for the benefit of society. The role of government is enormous and absolutely to determine the amount of royalties to the patent exploitation undertaken by the government issued Government Regulation No. 27 of 20014 About the Mechanism of Patent by the Government and Regulation of the Minister of Finance Ministry of Finance Regulation No. 72/PMK.02/2015 About Rewards Comes from Non Tax Revenue Royalties To Patent Inventor. Keywords : Intellectual Property Rights , Patents , Compulsory Licenses